Shishu Shiksha Karmasuchi for Quality Primary Education — An Analysis - Khanda, Subhasish (THE PRIMARY TEACHER, 2016)
5 * M. Phil scholar, Department of Education, RIE, Bhubaneswar, Odisha Abstract Universalisation of Elementary Education (UEE) has been one of the foremost objectives of the Government of India ever since Independence. But all children in the country do not get an opportunity to attend primary school due to various reasons. Besides, many drop out even after having been enrolled to a primary school. In order to rectify this situation and achieve the goal of UEE, the Government of West Bengal in the year 1997–98 planned to set up about 1,000 Child Education Centres with the help of Panchayati Raj bodies. The Department of Panchayat and Rural Development, West Bengal, took up the programme as Shishu Shiksha Karmasuchi and decided to set up Shishu Shiksha Kendras (SSKs) in areas, where at least 20 children did not have access to a primary school or required some special dispensation, which were not available in formal primary schools. Hence, Shishu Shiksha Karmasuchi aimed at mainstreaming out-of-school and other underprivileged children living in the remotest areas of West Bengal. The present study investigates the effectiveness of Shishu Shiksha Karmasuchi towards achieving the goal of UEE and various issues faced in implementing the programme at the primary level. The paper discusses various problems related to primary education and barriers like untrained teachers, irregular and inadequate supply of books and uniform, lack of parental involvement in school activities, and lack of infrastructure for Children With Special Needs (CWSN). All these create a hindrance in achieving the goal of UEE. Descriptive survey design was employed to conduct the study. Head teachers, teachers, academic supervisors, parents and School Management Committee (SMC) members were selected as participants through simple random sampling technique.